Chlorinated perfluoroalkyl ether sulfonate impairs proliferation and differentiation of neural stem cells via oxidative stress - Yaxin HAN; Longfei FENG; Zhijun ZHOU; Xiuli CHANG (环境与职业医学)
BackgroundChlorinated perfluoroalkyl ether sulfonate Cl-PFAES, trade name F-53B, a novel per- and polyfluoroalkyl substance (PFAS), has been shown to induce multi-organ toxicity in humans and cross the blood-brain barrier. However, its toxic effects and underlying mechanisms on neural stem cells (NSCs) remain unclear.ObjectiveTo investigate the impact of F-53B on NSCs proliferation and differentiation through oxidative stress and explore its potential molecular mechanisms in associations with mitochondrial function damage and the expression of autophagy-related gene (PINK1/Parkin).MethodsPrimary NSCs isolated from neonatal C57BL/6 mice were used as a model and exposed to F-53B at concentrations of 0, 33, or 100 μmol·L−1 for 24 h. Cell viability was assessed using the cell counting kit-8 (CCK-8) assay, while proliferation was evaluated by the 5-ethynyl-2’-deoxyuridine (EdU) incorporation assay. Immunofluorescence staining was performed to observe differentiation phenotypes. Intracellular and mitochondrial reactive oxygen species (ROS) levels were quantified using dihydroethidium (DHE) and MitoSOX probes, respectively. Mitochondrial morphology was observed using MitoTracker Green. ATP level was measured with a commercial kit. Additionally, real-time quantitative polymerase chain reaction (qPCR) was conducted to quantify the expression of PINK1 and Parkin genes.ResultsExposure to 100 μmol·L⁻¹ F-53B significantly reduced cell viability to 93.6% of the control group (P<0.01), and decreased the proportion of EdU⁺ cells (P<0.01), indicating proliferation inhibition. The differentiation analysis showed a reduction in neuronal generation, axonal shortening, and an increase in astrocytes. The 100 μmol·L−1 F-53B exposure elevated intracellular ROS to 122% (P<0.01) and mitochondrial ROS (MitoROS) to 135% (P<0.001) of the control levels, leading to mitochondrial fragmentation. The ATP levels after the F-53B exposure decreased to 62.4% relative to the control group (P<0.001). Furthermore, the mRNA expression levels of PINK1 and Par after the F-53B exposure were notably reduced (P<0.05).ConclusionF-53B may induce oxidative stress, thereby disrupting mitochondrial morphology and function while inhibiting the PINK1/Parkin-mediated mitophagy pathway, ultimately leading to impaired neural stem cell proliferation and abnormal differentiation. This study provides new insights into the neurotoxicity mechanisms of F-53B.